Recommendations on the Appropriate Management of Steroids and Discharge Planning During and After Hospital Admission for Moderate-Severe Ulcerative Colitis: Results of a RAND Appropriateness Panel. (13th August 2022) - Dulai, Parambir S.; Rai, Victoria; Raffals, Laura E.; Lukin, Dana; Hudesman, David; Kochhar, Gursimran S.; Damas, Oriana M.; Sauk, Jenny S.; Levy, Alexander N.; Sofia, M. Anthony; Tuskey, Anne; Deepak, Parakkal; et al.
Abstract : INTRODUCTION: Limited guidance exists for the postdischarge care of patients with ulcerative colitis hospitalized for moderate-severe flares. METHODS: RAND methodology was used to establish appropriateness of inpatient and postdischarge steroid dosing, discharge criteria, follow-up, and postdischarge biologic or small molecule initiation. A literature review informed on the panel's voting, which occurred anonymously during 2 rounds before and after a moderated virtual session. RESULTS: Methylprednisolone 40–60 mg intravenous every 24 hours or hydrocortisone 100 mg intravenous 3 times daily is appropriate for inpatient management, with methylprednisolone 40 mg being appropriate if intolerant of higher doses. It is appropriate to discharge patients once rectal bleeding has resolved (Mayo subscore 0–1) and/or stool frequency has returned to baseline frequency and form (Mayo subscore 0–1). It is appropriate to discharge patients on 40 mg of prednisone after observing patients for 24 hours in hospital to ensure stability before discharge. For patients being discharged on steroids without in-hospital biologic or small molecule therapy initiation, it is appropriate to start antitumor necrosis factor (TNF) therapy after discharge for anti-TNF-naive patients. For anti-TNF-exposed patients, it is appropriate to start vedolizumab or ustekinumab for all patients and tofacitinib for those with a low risk of adverse events. It is appropriate to follow up patients clinically within 2 weeks and with lower endoscopy within 4–6 months after discharge. DISCUSSION: We provide recommendations on the inpatient and postdischarge management of patients with ulcerative colitis hospitalized for moderate-severe flares.